Analisis Legitimasi Zakat Profesi dari Dimensi Syariah dan Regulasi di Indonesia (A Legitimation Analysis of Profession Zakat from Sharia and Regulation Dimensions in Indonesia) - Efri Syamsul Bahri; Mohd Mizan Mohammad Aslam; Hendro Wibowo (Jurnal Dakwah Risalah, 2020)
The total potential for zakat profession is IDR. 139.07 trillion, or 59.5 percent of Rp's total national zakat potential. 233.8 trillion. Meanwhile, the realization only reached IDR. 3.9 trillion or 2.8%. This study aims to analyze the zakat profession from the sharia and regulatory dimensions. This study uses a qualitative method with a descriptive approach and literature study. The research data was obtained by collecting and reviewing previous research results that were relevant to the theme. The results showed that zakat profession from the sharia dimension is obliged to follow the text of the Alquran and the fatwas of the ulama to meet the ‘nisab’ limit. Meanwhile, on the regulatory side, professional zakat is comprehensive. It is indicated by the presence of regulations at the macro, meso, and micro levels. Thus, professional zakat has strong legitimacy and can encourage optimizing the collection and distribution of zakat.